Norma Subyektif Dan Dukungan Teman Sebaya Terhadap Intensi Berhenti Merokok Pada Remaja Kota Depok - Achmad Lukman Hakim (Direktorat Politeknik Kesehatan Makassar, 2023)
Background: Basic Health Research Data for 2018, there were 52.1% of smokers who smoked for the first time at the age of 15-19 years. In addition, there are around 10.61% of the population aged 15-19 years who smoke in 2020, which is an increase from 10.54% in 2019. Objective: To determine the effect of subjective norms and peer support on the intention to stop smoking in adolescents in Depok City. Method: The type of research used is an observational analytic study using a cross-sectional research design. The study population was all adolescents who live in the Depok City Region in the 15-19 year age group of 166,445 people. Based on sample calculations using the Slovin formula, a minimum sample size of 399 respondents was obtained. The research instrument used a questionnaire, with data analysis using the Multiple Linear Regression hypothesis test. Results: There is an influence of subjective norms and peer support on the intention to stop smoking in adolescents in the Depok City Region in 2023 with an F-count of 780.178 and a p-value of 0.000 (<0.05). In addition, an R Square value of 0.798 was obtained, meaning that 79.8% of the intention to stop smoking was influenced by subjective norms and peer support, while the remaining 20.2% was influenced by other factors or other variables outside the model that were not examined. as the theory goes.